2001
DOI: 10.1074/jbc.m108181200
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Catabolism in Cancer Cells

Abstract: One of the most common signatures of highly malignant tumors is their capacity to metabolize more glucose to lactic acid than their tissues of origin. Hepatomas exhibiting this phenotype are dependent on the high expression of type II hexokinase, which supplies such tumors with abundant amounts of glucose 6-phosphate, a significant carbon and energy source especially under hypoxic conditions. Here we report that the distal region of the hepatoma type II hexokinase promoter displays consensus motifs for hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(126 citation statements)
references
References 23 publications
0
122
0
4
Order By: Relevance
“…1A). In contrast, hypoxia increased the expression of hexokinase II in SUM159 cells, a hypoxiainducible glycolytic enzyme (22), providing a positive control for the hypoxic environment (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…1A). In contrast, hypoxia increased the expression of hexokinase II in SUM159 cells, a hypoxiainducible glycolytic enzyme (22), providing a positive control for the hypoxic environment (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells preferably utilize anaerobic glycolysis for energy (18) and rely on both increased glucose transport across the cell membrane (19) and enhanced hexokinase activity (20) to meet higher glucose demand. Prior studies have reported on the variation of FDG uptake based on lung cancer grade 4 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, functional response elements for hypoxia (HIF-1), and p53 were located on the distal region of the promoter with the proximal region also being signficantly implicated in the hypoxic response (Mathupala et al, 1997a(Mathupala et al, , 2001). Reporter gene analysis also revealed an activation of the HK II promoter by glucose and the opposing metabolic hormones insulin and glucagon as well as cAMP analogs, the latter implicating the involvement of PKA and PKC pathways (Mathupala et al, 1995;Rempel et al, 1996b).…”
Section: Transcriptional and Post-transcriptional Events Related To Hmentioning
confidence: 99%